English English - Nahumury, Amanda Putri (ULTIMART Jurnal Komunikasi Visual, 2024)
As the result of a documentary film that highlights the meaning of Noken for the Papuan tribe, "Noken Rahim Kedua" experienced many challenges, both in the production, distribution and exhibition processes. This research aims to determine the challenges faced in the production, distribution and exhibition process of "Noken Rahim" Kedua documentary film. This research is a qualitative descriptive research with a case study research method that focuses on in-depth data collection interviews. In addition, the data analysis process in this research is using the Miles and Huberman model, which divided by three stages: data reduction, data display, and conclusion drawing. The research results show three important points. First, the production process of this film experienced various limitations, both in terms of time, costs, and personnel in the shooting process. Second, the distribution process of this film experienced many challenges because it could not be screened en masse because it was considered sensitive so there needed to be discussion during the screening. Third, the exhibition process is carried out through film festivals and screenings in alternative screening rooms. Keywords: documentary; film; film production; noken rahim kedua